2011
DOI: 10.1089/dna.2010.1198
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Association BetweenGSTM1andGSTT1Polymorphisms and Melanoma Susceptibility: A Meta-Analysis

Abstract: Glutathione S-transferases (GSTs) are a family of multifunctional enzymes that are involved in the metabolism of many xenobiotics, including a wide range of environmental carcinogens. The null genotypes GSTM1 and GSTT1 have been implicated in the development of carcinogenesis. We conducted a meta-analysis to examine the association of GSTM1 and GSTT1 homozygous deletion polymorphisms with melanoma risk. In total, 8 relevant studies were identified in searches of the PubMed and Embase databases: 8 investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
4
6
0
1
Order By: Relevance
“…Furthermore, GSTM1 polymorphism deletions are present in half the population, which may contribute to explaining their negative implication in MM onset. Our findings are consistent with several previous observations, recently collected in a meta‐analysis, which found no association between the GSTM1 and GSTT1 homozygous deletion polymorphisms or the GSTM1 – GSTT1 interaction and the risk of MM 34 . These findings indicate that neither homozygous deletion polymorphism is a risk factor for MM.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, GSTM1 polymorphism deletions are present in half the population, which may contribute to explaining their negative implication in MM onset. Our findings are consistent with several previous observations, recently collected in a meta‐analysis, which found no association between the GSTM1 and GSTT1 homozygous deletion polymorphisms or the GSTM1 – GSTT1 interaction and the risk of MM 34 . These findings indicate that neither homozygous deletion polymorphism is a risk factor for MM.…”
Section: Discussionsupporting
confidence: 93%
“…Both genes commonly harbour functional polymorphisms in the general population represented by gene deletions 18 . Frequencies of homozygous deletions of GSTM1 and GSTT1 were similar to those reported by other studies 34,35 . Despite being able to classify the exact number of copies, no association between GSTM1 and GSTT1 polymorphisms and MM risk was found.…”
Section: Discussionsupporting
confidence: 79%
“…These include meta-analyses that suggest GSTM1 deficiency increases the risk of head and neck cancer (Hashibe et al, 2003;Ye et al, 2004;Tripathy and Roy, 2006), cervical cancers (Gao et al, 2011;Liu and Xu, 2012) and oral cancer ). However, a number of meta-analyses indicated no marked association of GSTM1 null mutations with hepatocellular cancer (White et al, 2008), brain tumours (Sima et al, 2012), colorectal cancers (Zhao et al, 2012), ovarian cancers (Economopoulos et al, 2010), melanoma (Nie et al, 2011). In this study, the results indicate that null GSTM1 genotype might increase susceptibility to NPC which was in accordance with the evidence-based meta-analysis pertaining to GSTM1 and GSTT1 polymorphisms on nasopharyngeal cancer by .…”
Section: Discussionsupporting
confidence: 88%
“…These genotyping assays were performed together with two GSTP1 single nucleotide polymorphism (SNP) assays in a case–control study of 562 melanoma cases vs. 338 controls drawn from the Spanish population. The gene frequency data reported here confirm a recent meta‐analysis that neither GSTM1 nor GSTT1 genotypes are risk factors for melanoma 7 . However, homozygosity for the Ile105Val change in GSTP1 assayed as the rs1695*A/G SNP showed that the 105Val allele is independently associated with melanoma with an odds ratio (OR) of 1·32 [95% confidence interval (CI) 1·06–1·63].…”
Section: Original Article P 1176supporting
confidence: 82%